2016
DOI: 10.14814/phy2.12825
|View full text |Cite
|
Sign up to set email alerts
|

Urea transporters and sweat response to uremia

Abstract: In humans, urea is excreted in sweat, largely through the eccrine sweat gland. The urea concentration in human sweat is elevated when compared to blood urea nitrogen. The sweat urea nitrogen (UN) of patients with end‐stage kidney disease (ESRD) is increased when compared with healthy humans. The ability to produce sweat is maintained in the overwhelming majority of ESRD patients. A comprehensive literature review found no reports of sweat UN neither in healthy rodents nor in rodent models of chronic kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…While urea is a small molecule able to diffuse through and/or between cell walls, recent literature suggests that eccrine glands may express localized urea transporter subtypes (Keller et al 2016;Na et al 2019;Xie et al 2017). The expression of urea transporter 1 isoform 1 (UT-1) at the transcriptome and proteome level suggests the facilitation of transmembrane urea movement (Keller et al 2016;Xie et al 2017).…”
Section: Ureamentioning
confidence: 99%
See 2 more Smart Citations
“…While urea is a small molecule able to diffuse through and/or between cell walls, recent literature suggests that eccrine glands may express localized urea transporter subtypes (Keller et al 2016;Na et al 2019;Xie et al 2017). The expression of urea transporter 1 isoform 1 (UT-1) at the transcriptome and proteome level suggests the facilitation of transmembrane urea movement (Keller et al 2016;Xie et al 2017).…”
Section: Ureamentioning
confidence: 99%
“…While urea is a small molecule able to diffuse through and/or between cell walls, recent literature suggests that eccrine glands may express localized urea transporter subtypes (Keller et al 2016;Na et al 2019;Xie et al 2017). The expression of urea transporter 1 isoform 1 (UT-1) at the transcriptome and proteome level suggests the facilitation of transmembrane urea movement (Keller et al 2016;Xie et al 2017). UT-A1 and UT-B1 protein expression and localization have been found in cells of both the secretory coil (clear cells) and duct (Keller et al 2016), with significantly higher mRNA expression in uremic patients compared with normal controls (Xie et al 2017).…”
Section: Ureamentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of human sweat glands has some similarity with the convoluted tubules of the kidney and the composition of sweat is very similar with urine, also containing potassium, sodium, urea nitrogen, creatinine, uric acid, and other metabolic waste [ 1 ]. According to the fact that urea concentration in the sweat fluid was much higher than the serum level and the sweat urea concentration of CKD patients was dramatically increased [ 4 ], there must have been some mechanism to excrete urea out of the skin. The change of UTs in sweat glands of uremic patients is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, urea concentration in the sweat was much higher than the serum, which indicated that sweat is another way of expelling water and metabolic wastes besides urine. In particular, it was found that urea concentration was much higher in the sweat of chronic kidney disease (CKD) patients than that in normal people [ 3 , 4 ], indicating that the sweat glands play an important role in the water and metabolic wastes excretion in CKD patients.…”
Section: Introductionmentioning
confidence: 99%